Komposisi dan Struktur Tanaman Pekarangan Dataran Tinggi di Nagari Alahan Panjang Kabupaten Solok - Dwi Nofa Rina; - Chairul; - Solfiyeni (Jurnal Biologi Universitas Andalas, 2012)
This study was conducted from March to May 2012 at Nagari Alahan Panjang, Kecamatan Lembah Gumanti, Solok. The purpose of this study was to identify the composition and structure of home garden at Alahan Panjang. This study used purposive sampling method. The result shows that the composition of home garden plants consists to 49 families, 70 genus, 95 species and 3103 inviduals. Brassica oleracea was the most common species of vegetable plant with the highest value (15.381%) and diversity index was 3.88 which classified into the highest various criteria.Keywords: composition, structure, home garden, highland